2017
DOI: 10.1002/14651858.cd011396.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for raising breast cancer awareness in women

Abstract: Background: Breast cancer continues to be the most commonly diagnosed cancer in women globally. Early detection, diagnosis and treatment of breast cancer are key to better outcomes. Since many women will discover a breast cancer symptom themselves, it is important that they are breast cancer aware i.e. have the knowledge, skills and confidence to detect breast changes and present promptly to a healthcare professional. Objectives: To assess the effectiveness of interventions for raising breast cancer awareness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 67 publications
2
37
0
4
Order By: Relevance
“…There is potentially at least some effect of education sessions specifically targeted to increase BCA [ 25 ] although it remains unclear if these effects would be seen amongst women in rural settings in low-income countries. Despite this, it is reasonable to develop culturally sensitive and linguistically appropriate programs to promote BCA in low-income countries where screening (mammography or CBE) for early detection of breast cancer is currently not available.…”
Section: Discussionmentioning
confidence: 99%
“…There is potentially at least some effect of education sessions specifically targeted to increase BCA [ 25 ] although it remains unclear if these effects would be seen amongst women in rural settings in low-income countries. Despite this, it is reasonable to develop culturally sensitive and linguistically appropriate programs to promote BCA in low-income countries where screening (mammography or CBE) for early detection of breast cancer is currently not available.…”
Section: Discussionmentioning
confidence: 99%
“…El total de los estudios son de tipo cualitativo, tres de ellos se realizaron con un enfoque fenomenológico, uno hermenéutico y uno con la teoría fundamentada; el resto de estudios [13] no especifica el referente teórico-metodológico empleado. Las técnicas reportadas para la colecta de la información fueron: entrevistas semiestructuradas cara a cara [7], entrevistas vía electrónica [2], entrevista en profundidad [4], entrevista no estructurada [1], cuestionarios autoaplicados [3], grupos focales [1]; las preguntas fueron dirigidas a cuestionar la experiencia de ser cuidador de una mujer con cáncer. Para el análisis de los datos los artículos reportan el uso de análisis de contenido [4], temático [4], fenomenológico [2], análisis desde la teoría fundamentada [1], técnico [1], análisis de narrativa [2] y de interpretación básica [1]; los demás artículos [3] no definen el tipo de análisis de datos utilizado.…”
Section: Caracterización De Los Artículosunclassified
“…Las técnicas reportadas para la colecta de la información fueron: entrevistas semiestructuradas cara a cara [7], entrevistas vía electrónica [2], entrevista en profundidad [4], entrevista no estructurada [1], cuestionarios autoaplicados [3], grupos focales [1]; las preguntas fueron dirigidas a cuestionar la experiencia de ser cuidador de una mujer con cáncer. Para el análisis de los datos los artículos reportan el uso de análisis de contenido [4], temático [4], fenomenológico [2], análisis desde la teoría fundamentada [1], técnico [1], análisis de narrativa [2] y de interpretación básica [1]; los demás artículos [3] no definen el tipo de análisis de datos utilizado. El número de participantes de cada estudio osciló entre 6 y 91, con una media de 23; un estudio estuvo dirigido a cuidadoras mujeres, ocho incluyeron a hombres cuidadores cónyuges, dos investigaciones consideraron a la diada paciente-cuidador y los restantes [7] tuvieron como población de estudio a los cuidadores familiares en general.…”
Section: Caracterización De Los Artículosunclassified
“…In the past, screening by breast self-examination was recommended to all women, and an extensive effort was invested in teaching women how to conduct a monthly systematic selfexamination (Pennypacker et al, 1982). However, results of large trials found no beneficial effect of breast selfexamination; in fact, the opposite was found-evidence supporting increased harm including increased numbers of identified benign lesions and performed biopsies (O'Mahony et al, 2017). Therefore, a paradigm shift occurred-from breast self-examination to general breast awareness practices (BAPs;MacBride, Pruthi, & Bevers, 2012), which is now recommended by various national and international cancer and health organizations (O'Mahony et al, 2017).…”
Section: Scientific Backgroundmentioning
confidence: 99%